CYTOTOXIC EFFECT OF Brassica oleracea L. var. italica FLORETS AND MICROGREENS ON ACUTE LEUKEMIC CANCER CELL LINE (Applied Biological Research, 2024)
The bioactivity of broccoli microgreens might be valuable for understanding the   association between diet and cancer along with searching for healthy and   functional food options. The present study was centred on broccoli microgreens   as a functional food. The anticancer activity was measured in broccoli florets   and microgreens. The cytotoxicity of microgreens extract was confirmed by flow   cytometry assays. Significantly higher anticancer activity was observed in   microgreens as compared to the florets. The IC50 value for Thp-1 cell line was   772.47 and 446.34 µg mL-1for florets and microgreens, respectively. In cell cycle   analysis, 69% cells were arrested at G0/G1 phase. The 8.58% of dead cells were   detected in early apoptosis. As the cells were in early apoptosis, DNA damage   was observed only in 3.53% cells. Thus, the increased consumption of broccoli   microgreens could have significantly positive impact on human health.
Keywords: Broccoli microgreens, Cytotoxic effect, Cell cycle arrest, Apoptosis, Thp-1 cell line